Immunofluorescence (IF) pattern, autoantigens of anti-neutrophil cytoplasmic antibodies (ANCA) and their clinical associations - Masita Arip; Marlyn Mohammad; Salbiah Nawi; Shahnaz Murad (Penerbit UKM, 2010)
and monocytes’ lysosomes. In general, c-ANCA is strongly associated with vasculitic disorders mainly in ANCA-associated systemic vasculitis (AASV). p-ANCA have been identified in several diseases such as primary (AASV) and secondary vasculitis such as collagen vascular diseases, rheumatoid arthritis and inflammatory bowel diseases given the term ‘ANCA-associated disease.’ The objective of this study was to determine the rate of ANCA positivity by indirect immunofluorescent (IF) and enzyme linked immunosorbent assay (ELISA) and its association with AASV and ANCA associated diseases. Serum from patients with history suspicion of systemic vasculitis were tested for ANCA by IF. Those samples positive for ANCA by IF were further tested for antibodies against myeloperoxidase (MPO) and proteinase 3 (PR3) using the ELISA. Clinical data from medical records were obtained and analyzed. Of 468 samples, a total of 110 were positive for ANCA by IF. IF results showed a p-ANCA pattern in 96 patients and c-ANCA in 14. Of 110 IF positive ANCA, 45 patients were positive by ELISA. Seventeen were positive for MPO-ANCA, 9 were PR3-ANCA positive and 19 were both MPO and PR3 positive. Only 2 patients were classified AASV ie Wegener granulomatosis and the other with microscopic polyangiitis. The remaining patients (n = 108) may be classified as ANCA associated diseases. Our study showed that p- ANCA (87.3%) was the more common ANCA pattern and 40.9% of IF positive samples were positive for PR3- and MPOANCA.